Heritage education in times of COVID-19: an experience in students of the national school of merchant marine “Almirante Miguel Grau” - Quijano Araníbar, Iván Ernesto (2020)
The objective is to know the learning of local cultural heritage through the use of heritage research in Higher Education students in the virtual modality. The research approach is quantitative and the type descriptive. The nonexperimental cross-sectional design has been chosen. The sample is non-probalistic and consists of 70 students from the 1st cycle of the National School of Merchant Marine, enrolled in the virtual modality in the Cultural Activities course during the 2020-I semester. The survey was applied through the A1 instrument. The results show that student learning is as expected, given that there is a high assimilation of the heritage elements of Chucuito.